An 89Zr-HDL PET Tracer Monitors Response to a CSF1R Inhibitor - Mason, Christian A; Kossatz, Susanne; Carter, Lukas M; Pirovano, Giacomo; Brand, Christian; Guru, Navjot; Pérez-Medina, Carlos; Lewis, Jason S; Mulder, Willem J M; Reiner, Thomas (The Journal of nuclear medicine (1978), 2020)
The immune function within the tumor microenvironment has become a prominent therapeutic target, with tumor-associated macrophages (TAMs) playing a critical role in immune suppression. We propose an 89Zr-labeled high-density lipoprotein (89Zr-HDL) nanotracer as a means of monitoring response to immunotherapy. Methods: Female MMTV-PyMT mice were treated with pexidartinib, a colony-stimulating factor 1 receptor (CSF1R) inhibitor, to reduce TAM density. The accumulation of 89Zr-HDL within the tumor was assessed using PET/CT imaging and autoradiography, whereas TAM burden was determined using immunofluorescence. Results: A significant reduction in 89Zr-HDL accumulation was observed in PET/CT images, with 2.9% ± 0.3% and 3.7% ± 0.2% injected dose/g for the pexidartinib- and vehicle-treated mice, respectively. This reduction was corroborated ex vivo and correlated with decreased TAM density. Conclusion: These results support the potential use of 89Zr-HDL nanoparticles as a PET tracer to quickly monitor the response to CSF1R inhibitors and other therapeutic strategies targeting TAMs.The immune function within the tumor microenvironment has become a prominent therapeutic target, with tumor-associated macrophages (TAMs) playing a critical role in immune suppression. We propose an 89Zr-labeled high-density lipoprotein (89Zr-HDL) nanotracer as a means of monitoring response to immunotherapy. Methods: Female MMTV-PyMT mice were treated with pexidartinib, a colony-stimulating factor 1 receptor (CSF1R) inhibitor, to reduce TAM density. The accumulation of 89Zr-HDL within the tumor was assessed using PET/CT imaging and autoradiography, whereas TAM burden was determined using immunofluorescence. Results: A significant reduction in 89Zr-HDL accumulation was observed in PET/CT images, with 2.9% ± 0.3% and 3.7% ± 0.2% injected dose/g for the pexidartinib- and vehicle-treated mice, respectively. This reduction was corroborated ex vivo and correlated with decreased TAM density. Conclusion: These results support the potential use of 89Zr-HDL nanoparticles as a PET tracer to quickly monitor the response to CSF1R inhibitors and other therapeutic strategies targeting TAMs.